You have the following system of equations:
2x + 3y = -9
-7x + 2y = -21
In order to solve the previous system of equations, proceed as follow:
- multiply the first equation by -2 and multiply the second equation by 3:
(2x + 3y = -9)(-2)
-4x - 6y = 18
(-7x + 2y = -21)(3)
-21x + 6y = -63
- next, sum the previous equations:
-4x - 6y = 18
-21x + 6y = -63
-25x + 0 = -45
- solve the previous equation for x:
-25x = -45
x = -45/(-25)
x = 9/5
- now, replace the previous values of x into the first equation of the system and solve for y:
2(9/5) + 3y = -9
18/5 + 3y = -9
3y = -9 - 18/5
3y = -45/5 - 18/5
3y = -63/5
y = -21/5
Hence, the solution to the given system is:
x = 9/5
y = -21/5